Coeliac disease under a microscope: Histological diagnostic features and confounding factors. (January 2019) - Gibiino, Giulia; Lopetuso, Loris; Ricci, Riccardo; Gasbarrini, Antonio; Cammarota, Giovanni
Abstract: Coeliac disease (CD) and gluten-related disorders represent an important cornerstone of the daily practice of gastroenterologists, endoscopists and dedicated histopathologists. Despite the knowledge of clinical, serological and histological typical lesions, there are some conditions to consider for differential diagnosis. From the first description of histology of CD, several studies were conducted to define similar findings suggestive for microscopic enteritis. Considering the establishment of early precursor lesions, the imbalance of gut microbiota is another point still requiring a detailed definition. This review assesses the importance of a right overview in case of suspected gluten-related disorders and the several conditions mimicking a similar histology. Highlights: The diagnosis of coeliac disease requires a specific histopathological assessment. The mucosal architecture is the cornerstone of the histological classifications. Different confounding disorders should be considered in the differential diagnosis with coeliac disease. Dysbiosis could play a role in the activation of the immune system leading to the development of coeliac disease.